Local perceptions and adaptations to climate change and variability: Evidences from Southern Ethiopia - Yimam, Asnake; Mohammed, Yimer (International Journal of Environmental Sciences, 2016)
Purpose: climate change and variability is emerging as a serious global threat to the nation's future economic prosperity, environmental quality and social wellbeing. The overall aim of this study was to examine climate change and variability vulnerabilities and adaptation responses of local communities in southern Ethiopia. The specific objectives were to explore local peoples' perceptions and adaptation strategies towards climate change and variability and investigate factors influencing these endeavors across cultural and geographical contexts. Methodology: Four sample study areas were purposively selected for this study. The criteria for selection were presumed representatives of the Southern Ethiopia in terms of the various environmental attributes & presence of long term meteorological records with in the area. Both Qualitative and quantitative primary and secondary data were used in this study. The primary data was collected using questionnaire, focus group discussions, key informant interviews, in-depth case interview and direct observation. Secondary data (time series rainfall and temperature data spanning a period of 1987-2012) were obtained from Ethiopian National Meteorological Agency. Both quantitative and qualitative methods of data analysis were used. Results: The findings show that the increasing trend of temperature, unpredictable, erratic and decreasing trends of rainfall were perceived by most of the sample respondents. This result was in line with the meteorological records of temperature and rainfall data of most of the meteorological stations. The standardized annual rainfall anomalies showed that more than 50% of the annual rainfall was below the average annual rainfall record in almost all stations which indicated the occurrences of several worst meteorological droughts in various years. The analysis also revealed that age and educational levels were found to have significant influence on the perception and adaptation of climate change & variability. The adaptation strategies used in the area included adjustments in crop and livestock production as well as involving in other income generating options. Recommendations: The study suggests that more efforts should be geared to improve communities' education and create better institutional setup that enhance resilience, improve and sustain adaptation strategies to climate change & variability.